Enfarte Agudo do Miocárdio na Criança - Martins, V (1996)
A retrospective study was made of 6 children, with nonsurgical-related acute myocardial infarction (AMI), between January 1987 and December 1994. The ratio for gender was 1 and mean age at AMI was 49 days, 4 cases being associated with congenital heart disease (Fallot's tetralogy, truncus arteriosus and DiGeorge syndrome, one case each, and anomalous origin of left coronary artery, 2 cases). Kawasaki disease and coronary embolisation from thrombosis of the renal vein occurred in the other 2 cases respectively. All developed congestive cardiac failure and cardiomegaly. In the ECG pathologic q waves with more than 35 msec occurred in all, and QT prolongation occurred in 3. Five children (83%) all with AMI in the anterior and lateral wall of the left ventricle died, death being related with cardiac mechanical failure and not with arrhythmias.